[Ship Unloading Fish at Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a ship unloading fish at Heimaey harbor. The white ship covered in small, rounded windows and a line of Icelandic texts sit to the right alongside a dark platform to its left. A crane holds the chains of a rusted, metal container full of fish in the top left corner of the photograph. A mountain towers over the ship below, dark water surrounding it.